Clinical study of etomidate emulsion combined with remifentanil in general anesthesia - Weng D; Huang M; Jiang R; Zhan R; Yang C (Dove Medical Press, 2013)
Digui Weng, Menghua Huang, Runnian Jiang, Rufu Zhan, Chunni YangDepartment of Anesthesiology, Mindong Hospital Affiliated to Fujian Medical University, Fuan, Fujian, People's Republic of ChinaBackground: The aim of this study was to investigate and evaluate the safety, recovery time, and side effects of general anesthesia with different doses of etomidate emulsion combined with remifentanil.Methods: One hundred ten patients of American Society of Anesthesiologists class 1 or 2 who underwent gynecological general anesthesia with a 1-3-hour operation time were randomly divided into the following groups: etomidate emulsion group 1 ([E1] n = 30); etomidate emulsion group 2 ([E2] n = 30); etomidate emulsion group 3 ([E3] n = 20); and propofol group ([P group] n = 30). For induction of anesthesia, 0.3 mg/kg etomidate emulsion, and the continuous remifentanil infusion also to induce anesthesia (0.1~0.3 µg · kg-1 · min-1), was applied in all cases. Afterwards, continuous infusion of etomidate emulsion and remifentanil, respectively (E1: 10 µg · kg-1 · min-1 and 0.1 µg · kg-1 · min-1; E2: 15 µg · kg-1 · min-1 and 0.2 µg · kg-1 · min-1; E3: 20 µg · kg-1 · min-1 and 0.2 µg · kg-1 · min-1), and propofol (P group: 6~10 mg · kg-1 · h-1) were administered. Changes in blood flow kinetics and adverse reactions were noted and compared between the four groups.Results: Both arterial blood pressure (BP) and heart rate (HR) decreased after induction of anesthesia (P < 0.05). Systolic (SBP) and diastolic (DBP) BP changed only slightly, and HRs were slightly infected in E1, E2, and E3. SBP, DBP, and HR during the operation all decreased significantly in P group (P < 0.05). Muscle tremor at the time of induction occurred in 13 cases (11.8%). Following etomidate emulsion anesthesia maintenance, postoperative agitation occurred in seven cases (8.75%), lethargy in 20 cases (25%), and vomiting in 19 cases (23.75%). No adverse reactions were found in P group.Conclusion: Continuous infusion of etomidate emulsion at 10 µg · kg-1 · minute-1 combined with remifentanil during anesthesia has the advantages of hemodynamic stability, quick wake-up, and few adverse reactions. Increasing the dose of etomidate emulsion increases the incidence of adverse reactions.Keywords: etomidate emulsion, remifentanil, general anesthesia